A Pilot Investigation of Occupational Therapy Students’ Perceptions of Their Impact on Services to Older Adults - Li, Dongni; Nagarajan, Srivalli; du Toit, Sanetta (International Journal of Practice-based Learning in Health and Social Care, 2018)
Practice education is an integral component of occupational therapy curricula to ensure graduates are competent in delivering effective and efficient services to their clients. This study aimed to understand occupational therapy students’ perceptions of the impact of student-delivered services for clients aged over 65 years. A case study design directed at in-depth exploration of undergraduate occupational therapy student experiences of working with older adults was employed. Semi-structured interviews were conducted with eight final-year students at an Australian university during 2015. Data were analysed using thematic analysis. The key finding was that students generally believed they contributed positively to aspects of client-services during placements. Students reported on the development of competence during placement and the positive impact they had on services for older adults. The study highlighted the unique intergenerational relationship students had with older adults during their therapeutic encounters. However, very few participants recognised the importance and complexity of providing holistic services to older adults. Conclusion: There is potential to improve services for older adults by offering a greater number of placement opportunities involving students in direct client services. If occupational therapy students are better prepared, supported, and informed of the complexities associated with working with older adults, direct client-services rendered by students could potentially be enhanced. This will require ongoing collaboration between occupational therapy workforce, placement sites, and universities to align occupational therapy curricula with healthcare needs.